Akreditasi sebagai Instrumen Penjaminan Mutu dalam Dunia Pendidikan - Ardi Ansah Rambe; Zarkasih Efendi; Sahrul Gunawan; Joni Sejati Anugrah Pratama; Salfen Hasri; Sohiron Sohiron (CV. ALIM'SPUBLISHING, 2026)
Accreditation is an essential instrument in the educational quality assurance system that functions to assess the feasibility and continuously improve the quality of educational institutions. This study aims to analyze the role of accreditation as an instrument of educational quality assurance, examine the importance of accreditation for schools, and explain the mechanisms and procedures for completing accreditation instruments. The study employed a qualitative approach using a library research method. Data were collected from various primary and secondary sources, including books, scientific journals, research articles, laws and regulations, and other relevant academic documents. Data collection was conducted through documentation studies, while data analysis employed content analysis through the stages of data reduction, data presentation, and conclusion drawing. The findings indicate that accreditation plays a strategic role in improving educational quality through the evaluation of educational standards, strengthening quality culture, enhancing institutional accountability, and increasing public trust. Accreditation also encourages continuous improvement in curriculum development, learning processes, human resources, facilities and infrastructure, and school governance. Furthermore, a systematic accreditation mechanism assists schools in conducting self-evaluation and sustainable quality development. Therefore, accreditation serves not only as an assessment tool but also as an instrument for fostering and developing educational institutions in order to achieve high-quality and competitive education.